Optimized model development of a production process in a pharmaceutical laboratory applying integer mix linear programming with multiple objectives - Cuadros Segovia, Dante (2009)
The present article tries on the application of a model of mixed integer lineal programming with multiple objectives for the planning of the production system of a pharmaceutical laboratory, with the purpose of improving the taking of decisions when planning the production. It understands the description of the case of study, the considered suppositions, formulation of the model and the results of the same one.